A new non-LTR retrotransposon provides evidence for multiple distinct site-specific elements in Crithidia fasciculata miniexon arrays. - Teng, S C (1995)
We have identified a new member of the family of trypanosome site-specific retrotransposons, using a degenerate oligonucleotide PCR strategy. The 9595 bp element, termed Crithidia retrotransposable element 2 (CRE2), was cloned and found to be inserted in the tandemly arrayed miniexon genes of Crithidia fasciculata. The element is flanked by 29 bp target site duplications but lacks the 3' poly dA tract characteristic of most other non-long terminal repeat retrotransposons. The amino terminal region of the single 2518-codon open reading frame contains a putative metal-binding motif and a proline-rich region similar to gag-like domains of other retrotransposons. The carboxy terminal region of this open reading frame shares sequence homology with the reverse transcriptase and putative endonuclease regions of three previously described trypanosomatid site-specific retrotransposons. All four of these retrotransposons are specifically inserted between nucleotides 11 and 12 of the highly conserved 39mer sequence of the miniexon gene. Most copies of CRE2 and the previously characterized CRE1 are located on different sized chromosomes. Additional CRE-related sequences were identified by screening Crithidia libraries. These results suggest that a particular sequence in the C. fasciculata miniexon repeat is the target for multiple distinct site-specific retrotransposon insertions.